Thiopurinol: Comparative enzyme inhibition and protein binding studies with allopurinol, oxipurinol and 6-mercaptopurine - Dean, B. M. (1974)
1 The metabolites of thiopurinol have been investigated in intact human and pig erythrocytes using [6-(14)C]-thiopurinol, high voltage electrophoresis and automated cation exchange chromatography. 2 Pre-incubation of human erythrocytes in vitro with thiopurinol increased the formation of hypoxanthine from [8-(14)C]-inosine and simultaneously reduced IMP synthesis. 3 Reduced inosine formation, following one week of thiopurinol therapy, has also been observed in vitro using the intact red cells from three patients suffering from gout. 4 Binding of thiopurinol, and to lesser extents of 6-mercaptopurine, uric acid, oxipurinol and allopurinol, has been demonstrated electrophoretically to human and pig serum proteins. 5 Thiopurinol is shown to have a greater binding capacity for purified human serum albumin than uric acid or 6-mercaptopurine at varying substrate and albumin concentrations covering the physiological range. Under these conditions the binding of uric acid is reduced in the presence of thiopurinol. 6 A comparison of the distribution of thiopurinol, 6-mercaptopurine, allopurinol and oxipurinol in whole blood has revealed that allopurinol and oxipurinol are not irreversibly bound to cellular proteins; whereas 30% and 13% of the total cellular uptake was irreversibly bound in the case of thiopurinol and 6-mercaptopurine respectively at substrate levels of 1 nmol per μl blood.